CORPORATE PERFORMANCE: A PANEL DATA STUDY OF SELECTED COMPANIES - Sandhu, Hartaj Singh (My University, 2013)
India since Independence followed a very restrictive corporate policy till 1990-91 where private corporate sector had very little scope to grow and flourish due to socialistic pattern of industrial development in which profit was considered as a ‘dirty’ word. Followed by balance of payment crisis in early years of 1990s economic reforms initiated comprising a variety of deregulatory measures which significantly altered the environment in which the Indian corporate sector operated earlier. The economic reforms since 1991 have brought many changes to the environment in which Indian companies previously operated. The principal aim of these reforms was to strengthen market discipline and promote greater competition by putting an end to the “license raj,” namely through the abolition of the Industries Development and Regulation Act (1951) and amendments to the Companies Act and several other major laws, which had imposed a heavy legal and regulatory burden on the corporate sector. In addition, the foreign trade regime was liberalized through cuts in tariff rates, reductions in nontariff barriers, and a streamlining of import licenses; foreign investment opportunities were increased; and shareholders’ rights were improved. Indian companies were allowed to enter into joint ventures with multinational enterprises more freely, import new technologies and capital goods, expand productive capacity, and introduce new products without obtaining industrial licenses. More recently, steps have been taken to de-reserve a number of small-scale industries, particularly those industries with the greatest export potential. India’s corporate sector has grown steadily over the past two decades in terms of number of registered companies and amount of paid up capital. The corporate sector consists of closely held (private limited) and publicly held (public limited) companies, with approximately 619,000 registered companies as of June 2003, about 40 percent of which are in the manufacturing sector. Private limited companies comprise the majority of firms in the corporate sector, but account for less than one–third of total paid up capital Government-owned enterprises (both public and private limited) are comparatively few in number but large in size, accounting for more than 25 percent of the paid up capital. The share of total output by government enterprises has been declining since the start of reforms, falling from 32 percent of gross industrial value added in 1991 to 25 percent in 2002. India’s corporate sector is supported by a well-established equity market. Currently, there are 23 registered stock exchanges in India, with total market capitalization of US$131 billion at end–2002, equivalent to 26 percent of GDP and compared with 21 percent in 1990. The equity market is dominated by the Bombay Stock Exchange—the oldest in Asia—and the National Stock Exchange (NSE). The NSE began operations in 1994 in response to a government effort to improve the efficiency and transparency of India’s equity market. It quickly established itself as the foremost stock exchange in the country. Efforts are under way to close and/or consolidate a number of regional stock exchanges that have been generally thinly traded but largely sustained by listing requirements governing publicly traded companies operating in a different region. During the reform period, India’s corporate sector initially strengthened, but in recent years, it has shown signs of weakening in line with the slowdown in economic growth and industrial production. Though the pace of economic reform has faltered in recent years but the overall direction of policy change remains the same and seeks to strengthen market discipline and enhance competition. The success of the new policy regime was expected to and is likely to depend on the strategies adopted by firms in response to these policies and fine tuning of policies by taking cognizance of emerging trends in firm level choices. In this backdrop, this study tried to explain the performance of the Indian corporate sector during 2008 and 2012. We selected four sectors namely IT, FMCG, Infra and Healthcare sector for studying performance of the Indian corporate sector. From each sector, four companies were selected on the basis of their market capitalization from 2008 to 2012. Data on profit, sales turnover, total assets, debt/equity ratio, and return of assets were collected for the study. Statistical tools such as descriptive statistics, ANOVA, regression and panel data regression used for studying corporate performance in India. Results showed that corporate performance in India is explained by sales turnover and size of total assets of companies.
MP, SBSBS
Keywords: Corporate Performance; Panel Data